Real-time genome imaging of host interactions in adeno-associated virus genome release - Luisa F. Bustamante-Jaramillo; Lei Yue; Joshua Fingal; Gustaf Rydell; Maria Johansson; Tomas Edreira; Oliver J. Müller; Susanne Hille; Martin Müller; Franck Gallardo; Qingxin Chen; Marie-Lise Blondot; et al. (iScience)
Summary: Adeno-associated virus (AAVs) with a self-complementary genome (sc) comprising a gene of interest are used in gene therapy. Their efficiency is limited but the molecular factors contributing to this restriction are poorly understood. We utilized scAAV2 containing a fluorescent protein-binding anchor sequence on its genome allowing visualization of released genomes by time-lapse microscopy. Pairing this technique with capsid staining, we showed that scAAV2 genome release was initiated by a partial genome exposure, triggered by elevated calcium levels while the capsids interacted with proteins of the nuclear pore. Genome release occurred subsequently requiring Rad52 decamerization in the vicinity of the host chromatin. A fraction of the released genomes was degraded by Mre11, an essential factor for chromatin stability, and cellular DNA double-strand breaks. These steps were key-factors limiting transduction, suggesting that temporary modulation of DNA damage-response-proteins is a promising way to increase scAAV efficiency in therapy.